Estudos de três meios de cultura axênicos para a ferrugem das mirtáceas - Pizetta, Marilia [UNESP]; Pierozzi, Caroline Geraldi [UNESP]; Pereira, Gleice Viviane Nunes [UNESP]; Cruz, Juliana Cristina Sodário; Aparecido, Christiane Ceriani; Passador, Martha Maria [UNESP]; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2016)
Axenic cultivation has been shown as an important tool for studies related to the biology, the pathogenicity and the maintenance of pure cultures of biotrophic species. Therefore, the present study aimed to analyze the in vitro growth of Puccinia psidii uredospores, using enriched culture media that had success in the axenic cultivation of other rusts. Compounds such as salts, amino acids, carbohydrates and vitamins were selected for the preparation of three enriched culture media: ASZV Kuck (10), SH Schenk & Hildebrandt (21) and HG Harvey & Grasham (7), modified. Comparatively, enriched media were prepared from leaves of “jambeiro” (FJ) at four concentrations: 0.5; 1.0; 3.0 and 5.0 g L-1 (grams of leaves per one liter of distilled water). In this study, verification covered only the first stage of fungal growth, germ tube growth, not continuing in the pathogen development. The enriched media that provided greater P. psidii germ tube growth were the media ASZV, HG and FJ at 0.5 g L-1 concentration.
Study of three axenic culture media for rust in Myrtaceae
Keywords: Biotrophic cultivation; Myrtaceae; Puccinia psidii